EFEKTIVITAS KOMUNIKASI INTERNAL CORPORATE COMMUNICATIONS DALAM MENYEBARLUASKAN INFORMASI KEPADA KARYAWAN DI PT RIAU ANDALAN PULP AND PAPER - Saputra, Randi; Rasyid, Anuar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Internal communication is a communication that occurs within the office or organization. Communication is one important aspect to realize the company's goals. A communication occurs because there is a structure within an organization and this is supported by various internal corporate communication media. PT RAPP is a subsidiary of APRIL Group which already has a special division to handle internal communications company that is Internal Communications Officer. This division belongs to the Corporate Communications Department. According to the theory of information organization by Wick, the purpose of this study is to find out how much the level of effectiveness of communications internal corporate communications PT RAPP in providing information to employees.The method used in this study is mix method which means quantitative method supported by qualitative method. Data collection by distributing questionnaires to 100 of PT RAPP employes from 4500 all populations and using proportional random sampling technique. For data analysis in this research use descriptive statistic technique.Based on the concept of communication effectiveness according to Hardjana indicator in this research that is message source, message content, media, receiver or user, format and timing. The results of this study indicate the level of effectiveness of corporate communications internal communications PT RAPP in providing information to employees classified as very effective in range 3,26. There has a communications model, support and obstacle factor and some communications chanel in informations distributed by internal communications officer around companyKeyword : Effectivity, Internal Communications, Mix Methode